2009
DOI: 10.1097/aap.0b013e31819a12ba
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Observational Study of the Relationship Between Body Mass Index and Depth of the Epidural Space During Lumbar Transforaminal Epidural Steroid Injection

Abstract: Background and Objectives-Previous studies have concluded that transforaminal epidural steroid injections (ESIs) are more effective than interlaminar injections in the treatment of radiculopathies due to lumbar intervertebral disk herniation. There are no published studies examining the depth of epidural space using a transforaminal approach. We investigated the relationship between body mass index (BMI) and the depth of the epidural space during lumbar transforaminal ESIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
(15 reference statements)
0
15
1
1
Order By: Relevance
“…In a more recent study, Brummett et al. concluded that the distance from skin to lumbar epidural space measured via a transforaminal approach (similar to the paramedian approach) is greater than that obtained via an interlaminar approach [13]. Our study addresses these sources of bias by exclusion of labour epidurals performed in the lateral position and via the paramedian approach.…”
Section: Discussionmentioning
confidence: 92%
“…In a more recent study, Brummett et al. concluded that the distance from skin to lumbar epidural space measured via a transforaminal approach (similar to the paramedian approach) is greater than that obtained via an interlaminar approach [13]. Our study addresses these sources of bias by exclusion of labour epidurals performed in the lateral position and via the paramedian approach.…”
Section: Discussionmentioning
confidence: 92%
“…The procedures were performed according to the subpedicular transforaminal technique (ISIS Practice Guidelines [23]). The patient was positioned prone and skin was prepped with sterile technique.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Brummett et al [23] found that needle length increases with BMI when performing TFESI, and practitioners anecdotally report increased difficulty controlling longer length needles. Additionally, interventionalists often report increased difficulty visualizing targets when performing TFESI in individuals with a larger body habitus.…”
Section: Introductionmentioning
confidence: 99%
“…En las pacientes embarazadas obesas se pueden presentar mayores dificultades técnicas para la punción neuroaxial en comparación con las de peso normal, por mala identificación de reparos anatómicos (línea media de la columna vertebral, línea intercrestal o de Tuffier, espacios intervertebrales, etc.) y aumento de la distancia entre la piel y el espacio epidural (31,32), lo que generaría mayor número de intentos durante la punción espinal y epidural (33). Por otro lado, en las embarazadas obesas existe mayor incidencia de desplazamiento del catéter epidural, falsos positivos generados por el panículo adiposo cuando se utiliza la técnica de pérdida de resistencia para la localización del espacio epidural, mayor incidencia de punción venosa peridural y de meninges (34), y mayor dificultad en el posicionamiento de la paciente previo a la realización de la punción neuroaxial.…”
Section: Anestesia En El Trabajo De Partounclassified